2020 International Society of Hypertension global hypertension practice guidelines. Issue 6 (June 2020) - Unger, Thomas; Borghi, Claudio; Charchar, Fadi; Khan, Nadia A.; Poulter, Neil R.; Prabhakaran, Dorairaj; Ramirez, Agustin; Schlaich, Markus; Stergiou, George S.; Tomaszewski, Maciej; Wainford, Richard D.; Williams, Bryan; et al.
Abstract : Document reviewers: Hind Beheiry (Sudan), Irina Chazova (Russia), Albertino Damasceno (Mozambique), Anna Dominiczak (UK), Anastase Dzudie (Cameroon), Stephen Harrap (Australia), Hiroshi Itoh (Japan), Tazeen Jafar (Singapore), Marc Jaffe (USA), Patricio Jaramillo-Lopez (Colombia), Kazuomi Kario (Japan), Giuseppe Mancia (Italy), Ana Mocumbi (Mozambique), Sanjeevi N.Narasingan (India), Elijah Ogola (Kenya), Srinath Reddy (India), Ernesto Schiffrin (Canada), Ann Soenarta (Indonesia), Rhian Touyz (UK), Yudah Turana (Indonesia), Michael Weber (USA), Paul Whelton (USA), Xin Hua Zhang, (Australia), Yuqing Zhang (China).